A global gaze : lesbian, gay, bisexual, transgender and intersex grantmaking in the global South and East (2007) - Espinoza, Robert (New York : Funders for lesbian and gay issues, 2008)
Fonds Suzan Daniel (FSD)
Engels
Brochure